2017
DOI: 10.14202/vetworld.2017.302-310
|View full text |Cite
|
Sign up to set email alerts
|

Effect of peripartum nutritional management on plasma profile of steroid hormones, metabolites, and postpartum fertility in buffaloes

Abstract: Aim:The aim of this study was to evaluate the influence of peripartum protein and minerals supplementation on plasma profile of steroid hormones, metabolites, and fertility in rural buffaloes.Material and Methods:A total of 85 advanced pregnant (~8 months) pluriparous buffaloes selected at farmers’ doorstep in three tribal villages of Middle Gujarat were randomly divided into two groups, viz., control (n=45) and nutrients treatment (40). The buffaloes of treatment group (n=40), in addition to farmers feeding s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
15
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 14 publications
22
15
2
Order By: Relevance
“…Dietary supplementation of fat increases the circulating concentrations of cholesterol, which serves as a precursor for the synthesis of progesterone by ovarian luteal cells and also increases the lifespan of induced CL (Rahbar et al, 2014). The gradual rise in mean plasma progesterone level on day 45 and 60 postpartum in the present study is supported by the findings of previous workers (Dhami et al, 2017;Kalasariya et al, 2017), who also observed gradual rise in progesterone prior to first postpartum estrus in cattle and buffalo.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…Dietary supplementation of fat increases the circulating concentrations of cholesterol, which serves as a precursor for the synthesis of progesterone by ovarian luteal cells and also increases the lifespan of induced CL (Rahbar et al, 2014). The gradual rise in mean plasma progesterone level on day 45 and 60 postpartum in the present study is supported by the findings of previous workers (Dhami et al, 2017;Kalasariya et al, 2017), who also observed gradual rise in progesterone prior to first postpartum estrus in cattle and buffalo.…”
Section: Resultssupporting
confidence: 93%
“…The present significant decreasing trend prepartum and increasing trend postpartum of plasma progesterone concentrations observed in buffaloes during transitional period corroborated with the earlier findings of Ullah et al (2010), Ashmawy (2015) and Kalasariya et al (2017) in buffaloes and Gowda et al (2015) and Dhami et al (2017) in cattle. In the present study, the basal value of progesterone found on the day of calving was suggestive of complete luteolysis at parturition and corroborated with the findings of Momongan et al (1990) and Kalasariya et al (2017).…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations